Efecto de tres dietas de proteína pura de origen animal, sobre el estado productivo en codornices Coturnix coturnix japónica en la etapa de postura. - Vásquez Medina, María Lourdes (2019)
With the objective of evaluating the effects in three diets of pure protein of animal origin, on the productive state in quails in the stage of posture in the production and quality of the egg. We used 500 Japanese quail of 1day of age, distributed in a Design of Blocks Completely Random (DBCA), with 4 treatments, 5 repetitions and 25 birds per repetition, evaluated during 9 weeks. The experimental diets were isoenergetic and isoproteic with 2800 Kcal ME / kg and 20% protein. The treatments were: T1 = 0% proteika 60%, T2 = 2.5% proteika 60%, T3 = 5% proteika 60% and T4 = 7.5% proteika 60%. The results showed in the consumption by bird, egg weight, egg mass, conversion, posture and weight of the bird significant statistical differences during all evaluation period, but for the food consumption and mortality they did not present significant statistical differences. In conclusion, it could be said that the best parameters were obtained when proteika 60% (2.5%, 5% and 7.5%) is added to the quail diet, but it is determined that the levels of 5% and 7.5% are the most beneficial for poultry farming because it has better economic retribution.